Walinong Sari Collection / Nurhana ‘Alyaa Johari - Johari, Nurhana ‘Alyaa (2020)
Regarding to fulfil Fundamental of Entrepreneurship (ENT300) course requirement, I need to carry out a case study. During a case study, I need to collect all information about a company to complete study case, so I decide to contact WALINONG SARI COLLECTION Manger to do an interview session with the president or the owner who is Datuk Shuhaini Shafie. WALINONG SARI COLLECTION is a company that produces products called Clothing (brand). From the interview I have known about their background of the business,organizational structure, type of business model, product or services marketing and operational strategy. Besides that, I also enable to analyses the Entrepreneurial Characteristic.